Optimisation of Machining Parameters in Turning AISI 304L Stainless Steel by the Grey-Based Taguchi Method - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2017)
In this study, an experimental optimization of cutting forces and surface roughness in turning of AISI 304L stainless steel using wiper and conventional insert cutting tools with dry cutting conditions are presented. The influences of feed rate, depth of cut, and corner radius on surface roughness, cutting force and surface hardness are examined. In order to optimize the turning process, Grey relational analysis optimization method is used. The optimal machinability conditions of AISI 304L stainless steel with coated carbide insert are successfully determined in this study.
Keywords: SURFACE-ROUGHNESS; CUTTING FORCE; TOOLS; WIPER